Cyclic soil-structure interaction of integral railway bridges - Stastny, Alexander; Emera, Anas; Galavi, Vahid; Tschuchnigg, Franz (Frontiers in Built Environment, 2025)
Integral bridges with larger spans experience increased cyclic interaction with their backfill, particularly due to seasonal temperature changes. This can result in a continuous increase of earth pressure (during the summer positions) as well as an accumulation of settlements in the granular backfill over the bridge’s lifespan. While the soil stresses must be accounted for in the structural design through appropriate calculation methods, the settlements negatively impact the serviceability and the maintenance demands of the railway track and can only be accepted to a very limited extent. Therefore, this paper presents a detailed numerical investigation on the cyclic interaction behavior of integral railway bridges. For this purpose, an elastoplastic soil material model (DeltaSand), which has been calibrated based on a comprehensive experimental program for a well-graded gravel backfill material, and validated 2D and 3D FE models are used. Extensive parametric studies are conducted with varying bridge geometries (lengths, heights), as well as abutment, backfill, and foundation stiffnesses. The numerical results for both, the lateral stress loading and the bending moment of the abutment are compared to analytical design approaches used in Germany, Austria and United Kingdom. Lateral stresses on the abutment and settlements of the backfill show a clear increase with cycles and bridge lengths. The stiffness of both the backfill material and the underground soil highly influences the earth pressure mobilization and its distribution on the abutment. The study also highlights that existing design approaches are not conservative in all cases and should be adjusted.